A dispersive liquid–liquid microextraction followed by reverse‐phase high‐performance liquid chromatography for QuEChERS determination of chlorogenic acid. Issue 1 (23rd September 2022) - Amin, Mujahid; Sharif, Shahzad; Akram, Sumia; Muhammad, Gulzar; Amin, Saqib; Ashraf, Rizwan; Mushtaq, Muhammad
Abstract: Introduction: The presence of chlorogenic acid (CGA) not only imparts a characteristic flavour to foods but also makes them useful against chronic diseases and metabolic syndromes, especially diabetes mellitus and asthma. Objectives: The present study was designed to develop a quick, easy, cheap, effective, rugged, and safe (QuEChERS) and pragmatic method to analyse CGA in plant‐based products by applying dispersive liquid–liquid microextraction (DLLME) followed by reverse‐phase high‐performance liquid chromatography under a diode array detector (RP‐HPLC‐DAD). Methodology: The DLLME was carried out using Triton X‐100 as a dispersant and ethanol as an extraction solvent, while method development and validation activities were performed on a Shimadzu 10‐AT HPLC‐DAD system equipped with C‐18 columns as stationary phases. Results: The well‐resolved peak for the standard CGA was observed at 2.92 min for the mobile phase comprising 0.1% aqueous formic acid‐ethanol (22:78 v/v) of pH 3.0 programmed under an isocratic flow rate of 1.0 mL/min. The developed method was found to be linear (R 2  = 0.9976) over 1–500 μg/mL of CGA concentration at 328 nm. Moreover, the assay was found to be repeatable with RSD ≤ 5.0, and the limit of detection (LOD) and limit of quantification (LOQ) were 0.0281 and 0.0853 μg/mL of CGA, respectively. The DLLME offered an overall recovery rate between 97.60% and 99.54% at an acceptable level of reproducibility [relative standard deviation (RSD) ≤ 5.0]. Conclusion: The developed assay was found to be a QuEChERS and pragmatic choice for the high‐throughput analysis of CGA in plant‐based products/foods. Finally, the analysis revealed the presence of an ample level of CGA in guava fruit in addition to coffee beans and black tea. Abstract : The present study describes a dispersive liquid–liquid microextraction‐reverse‐phase high‐performance liquid chromatography under a diode array detector (DLLME‐RP‐HPLC‐DAD)‐based method to analyze chlorogenic acid in plant‐based products. The DLLME offered an overall recovery rate between 97.60% and 99.54% at an acceptable level of reproducibility (relative standard deviation [RSD] ≤ 5.0). The assay was found to be QuEChERS and pragmatic with limit of detection (LOD) and limit of quantification (LOQ) of 0.0281 and 0.0853 μg/ml. The analysis revealed the presence of ample levels of chlorogenic acid in guava fruit in addition to coffee beans and black tea.